MSN Model – Approach in The Implementation of Waste Management Policy in The City of Serang - Hasanah, Budi; Yulianti, Rachmi (Indonesian Journal of Social Science Research, 2025)
The issue of waste remains a national and even global concern. This is partly due to the increasing volume of waste that is not accompanied by proper and sustainable waste management. This waste problem is also felt by the community in Serang City, Banten Province. The objective of this study is to determine and analyse the implementation of waste management policies in Serang City using the MSN approach model. The method used in this study is descriptive qualitative with MSN approach analysis in the implementation of waste management policies according to Kadji with three approaches, namely mentality, systems, and networking. Data sources were obtained from primary data through interviews and discussions at scientific forums and secondary data through literature searches from the internet, books, and relevant journals. The results of this study indicate that waste management in Serang City has not been optimal, partly due to the absence of operational local regulations, including regulations discussing social entrepreneurship, particularly in waste management. In addition, not all stakeholders involved in waste management, including MSME actors, have been included. However, the Serang City Government, particularly the DLH, is still focused on establishing massive cooperation with educational institutions and creating a thousand waste banks in Serang City